Tobacco attributable morbidity and hospital costs in Piedmont: forecast for the years 2003-2014 (Italian Journal of Public Health, 2007)
Background: Tobacco smoke is the main cause of mortality and morbidity in most industrialized countries. The aim of this study is to forecast the smoke-related morbidity for the residents in Piedmont for the years 2003-2014 and the relative costs for the regional health service, using as an indicator the number of hospital admissions caused by smoke and as an instrument the DRG rates.Methods: The model uses the risk of hospitalisation among non smokers to predict smoke related morbidity for the period 2003-2014 for both smokers and ex-smokers, by using relative risks (RRs) and smoking prevalence. It should be noted that, because of the 15-year latency between smoke exposure and health outcomes, smoking prevalence of the appropriate time period has been applied to the morbidity data of the following 15 years, thus because of the shift of birth cohorts we are able to make forecasts up until the year 2014. Basing on these data it is possible estimate, separately for smokers and ex-smokers, the aetiological fraction (PAR%) used to estimate smoking attributable admissions and smoking attributable costs. The costs attributable to admissions for smoke-related diseases have been estimated using prices set for 2002 as well as prices adjusted for inflation.Results: A total of 145801 hospitalizations are expected among men and 36959 among females for the period 2003-2014. The economic value of the attributable admissions, at prices adjusted for inflation, increases in the period 2003-2014 with a slowdown in 2014. Data show that in 2014, compared to 2003, a smaller amount of resources, in true value, have been allocated to smoking related admissions (- 11.08%).Conclusions. The model used meta-analytic RR real prevalence data, considering a fifteen-year latency period between exposure and its effect on health. Furthermore, an economic estimate is made for each DRG instead of applying medium rates for Major Diagnostic Categories as is frequently seen at a national level.
Keywords: Smoking; attributable morbidity; hospital costs; forecasts